Pemanfaatan Limbah Pertambangan dan Industri Mineral sebagai Material Geopolimer untuk Aplikasi Konstruksi Tambang Berkelanjutan: Kajian Literatur Berbasis Studi Eksperimental - Venty Lestari; Andrawina Andrawina (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Mining and mineral processing wastes, such as tailings, fly ash, red mud, slag, and coal gangue, have the potential to be utilized as geopolymer materials to support sustainable mine construction. This article aims to review the utilization of mining and mineral processing wastes as geopolymer materials based on experimental research articles. The review was conducted by searching and analyzing 15 research articles that discuss material characteristics, compressive strength, microstructure, reaction products, heavy metal leaching, and the applications of waste-based geopolymers. The findings show that aluminosilicate-based wastes can be used as precursors, substitution materials, fillers, or supporting components in geopolymer systems. Reaction products such as N-A-S-H, C-S-H, and C-A-S-H play an important role in forming the binding matrix, increasing microstructural density, and improving material strength. Waste-based geopolymers also have potential applications as building materials, mortars, road subgrade materials, cemented paste backfill, and hazardous waste stabilization materials. In addition, the geopolymerization process can support heavy metal immobilization through physical encapsulation, chemical binding, adsorption, precipitation, and ion substitution mechanisms. However, its application in Indonesia still requires further studies related to local waste characterization, mix optimization, long-term durability, leaching behavior, technical standards, and economic and environmental feasibility.